Une frontière en guerre. Basques de France et d’Espagne face à la Première guerre carliste (1833‑1840) - Alexandre Dupont (Les Cahiers de Framespa)
This paper examines the upheavals and transformations brought about by the civil war between absolutists and liberals in Spain in the 1830s, which took place primarily in Navarre and the Basque provinces close to the French border. Like any civil war, this internal conflict in Spain called into question the socio‑political and territorial cohesion of the southern side of the Pyrenees, but the situation also affected the French border territory in many ways: the civil war extended beyond Spain's borders, destabilizing traditional cross‑border social activities, movements and exchanges. Faced with this situation, the border populations did not remain passive and resorted to adaptation strategies that also had to take into account the efforts of the French and Spanish authorities to make the border safe and hermetic, and to prevent the conflict from spreading north of the Pyrenees.